(untitled) (Journal of Hama University, 2025)
This study was carried out in Latakia Governorate (Fidio livestock farming) / in 2022 AD / to investigate the effect of four levels of biochar (0-100-300-600 kg dunum-1) and three levels of olive mill wastewater (5-10 l m-2) on some growth and productivity parameters of the Sb44 soybean plant and its seeds content of macronutrients growing in Loamy soil. The results showed that olive mil wastewater additions alone affected the growth and productivity indicators of soybean plant to a greater extent compared to the addition biochar alone. The co-application of olive mill wastewater at 10 l m-2 with biochar at 600 kg dunum-1 resulted in the highest plant height cm, leaf area index and productivity with increments by 45.43, 52.26 and 122.14%, respectively in comparison to the control. Soybean seeds content of macronutrients g100 g-1 increased with gradual biochar and olive mill wastewater increments reaching the maximum at 600 kg dunum-1 of biochar and 10 l m-2 of olive mill wastewater where the phosphorous, potassium and nitrogen rose by 63.14, 47.32, 25.05%, respectively in comparison to the control.